Implementation of Hadith Learning in Fostering the Diversity of Students at SMP IT Raudhatul Ulum Sakatiga Palembang - Triansyah, Arief Agus; Annaqsyabandy, Bahaudin; Gunawan, Wawan; Alkayisy, Muhammad Ilyas (AS-SABIQUN, 2023)
The goal to be achieved from the implementation of Hadith lessons at SMP IT Raudhatul Ulum is to foster the diversity of students, to make students who live in an orderly and obedient manner adhere to the Islamic religion and students who are obedient in worship aretiqomah. The hope of this Hadith lesson is to make students who are "IHSAN" worship you to Allah as if you see Allah and if you cannot see Allah Allah sees you. Whereas in terminology the two ihsan stand for Imtaq and Science and Technology, Harmonious, Polite, Enthusiastic and Comfortable. The method used in this research is a qualitative descriptive analysis method with the main source being relevant studies. The implementation of Hadith lesson in IT Raudhatul Ulum Middle School can foster the diversity of students, this is evidenced by students starting to practice Hadith science lessons such as congregational prayers, Dhikr and Du'a after prayer, willing to listen to Islamic religious advice, Tahajut and Witir prayers and clean life.